Starotestamentalne cuda w poemacie "Paschale carmen" Seduliusza - Krynicka, Tatiana (Vox Patrum, 2014)
Before turning to the wonderful Saviour’s deeds, that he strives to praise in Paschale Carmen, Sedulius introduces his reader into the old testamental history of salvation. In the Book 1, which fulfils the functions of a preface to the poem, he recounts 18 miracles that took place before Christ was born, since the ages of the Patriarchs to the period of the Babylonian captivity. These relations appear to be separate, self-contained stories. The longest is devoted to the miraculous fate of the prophet Elijah (lines 170-187); in the shortest the poet tells about the Balaam’s donkey, an animal without speech, who spoke to its master with a human voice (lines 160-162). Miracles fascinate Sedulius as extraordinary events, which deny the laws of nature and contradict common sense. At that they are sometimes connected with a marvelous metamorphosis. God performs miracles in order to show to the mankind His might, providence and kindness; to educate human beings and to prepare them for the coming of Christ; to foretell cosmic redemption at the end of times. Telling about the old testamental miracles Sedulius tends to refer both to the unbelievers and to the believers the revealed truth. He also aims to awake in the readers’ hearts wonderment, gratitude, love and trust towards the Holy Trinity.